Organizational and legal attributes of subjects of the authorities in the field of civil aviation of Ukraine - Pyvovar, Yuriy; Husar, Olga; Ustynova, Iryna (International Journal of Engineering and Technology, 2018)
In this paper, a concept and attributes of subjects of the authorities in the field of civil aviation have been defined. It has been determined that public authorities are a complex, dynamical, hierarchically constructed, multifunctional system of a state-legal nature. Aviation safety is an integral attribute of this system. The classification of aviation transportation subjects according to the legislation of the United States of America and the standards of the International Civil Aviation Organization has been given. The methods of system analysis, formally-juridical and a method of classification have been used. It has been suggested to improve the Air legislation of Ukraine in accordance with the ICAO requirements.Â Â